2019
DOI: 10.14202/vetworld.2019.1240-1250
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of sausage in Algeria: Prevalence, quality assessment, and antibiotic resistance of Staphylococcus aureus isolates and the risk factors associated with consumer habits affecting foodborne poisoning

Abstract: Aim: The first aim was to assess the quality and determine the prevalence and antibiotic susceptibility of Staphylococcus aureus contamination of raw sausage sold in ten municipalities in the Northeast of Algeria. Second, a consumer sausage purchasing survey was designed to investigate potential risk factors that have a significant association with the occurrence of foodborne poisoning among sausage consumers' behavior and its relationship with independent variables. Materials and Methods: A total of 230 butc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 60 publications
2
9
2
2
Order By: Relevance
“…This study reports the occurrence of S. aureus in the beef and frozen chicken which could account for economic loss and public health challenge of the consumers similar to the earlier report of Hachemi et al [8] and Wang et al [24]. S. aureus was isolated from beef and chicken in which occurrence was high in chicken compare with beef in this study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study reports the occurrence of S. aureus in the beef and frozen chicken which could account for economic loss and public health challenge of the consumers similar to the earlier report of Hachemi et al [8] and Wang et al [24]. S. aureus was isolated from beef and chicken in which occurrence was high in chicken compare with beef in this study.…”
Section: Discussionsupporting
confidence: 87%
“…Food is the good material for the proliferation and colonization of disease-causing microorganisms due to the easy provision of the essential nutrients required by microbes to grow [1][2][3][4][5][6]. Among the food-borne pathogens, Staphylococcus aureus is one of the common causative agents of foodborne diseases [7,8] and have successfully acquired resistant genes that enable them to be resistant to different antibiotics especially β-lactams [9]. S. aureus remains an important pathogen responsible for food-borne illness in human medicine, being globally disseminated.…”
Section: Introductionmentioning
confidence: 99%
“…S aureus strains (29.46%) showed a resistance to cefoxitin and were thus identified as methicillin-resistant S. aureus (MRSA) strains as described by Hachemi et al (2019). Radwan et al (2015) reported high rate of methicillin resistance with 58.3%.…”
Section: Evaluation Of Antibacterial Activitymentioning
confidence: 99%
“…Staphylococcus aureus is an important agent of subclinical mastitis in dairy animals. It is known as one of the leading causes of foodborne illness and food poisoning outbreak worldwide [1]. The presence of S. aureus and genes encoding staphylococcal enterotoxin (SE) in livestock products is hazardous for consumer health [2].…”
Section: Introductionmentioning
confidence: 99%